Usaha Perbankan Dan Asuransi - zailani . (AGHNIYA : Jurnal Ekonomi Islam, 2019)
The modern world is characterized by the proliferation of technology to make it easier for humans to carry out their routines. Talk between one another is faster and easier. About this is Muamalah. Islamic view, human and human relationship is called muamalah. One form of muamalah is the Banking and Insurance business. Basically, that should be based on the principle of honesty and justice. For the Banking and Insurance business, the legal status will be announced. Until now it has become a juridical foundation. Some allow and some forbid. The article will parse the position of Banking and Insurance in the view of Islam. Thus helping Muslims to carry out transactions in banking, insurance is full of security in its implementation and the law. By using the sources of the Koran and Sunnah and supported by the views of scholars who are experts in their fields.